Amorphous Mo‐doped NiS0.5Se0.5 Nanosheets@Crystalline NiS0.5Se0.5 Nanorods for High Current‐density Electrocatalytic Water Splitting in Neutral Media. (2nd January 2023) - Wang, Yang; Li, Xiaopeng; Huang, Zhong; Wang, Haozhi; Chen, Zelin; Zhang, Jinfeng; Zheng, Xuerong; Deng, Yida; Hu, Wenbin
Abstract: It is vitally important to develop highly active, robust and low‐cost transition metal‐based electrocatalysts for overall water splitting in neutral solution especially at large current density. In this work, amorphous Mo‐doped NiS0.5 Se0.5 nanosheets@crystalline NiS0.5 Se0.5 nanorods (Am−Mo−NiS0.5 Se0.5 ) was synthesized using a facil one‐step strategy. In phosphate buffer saline solution, the Am−Mo−NiS0.5 Se0.5 shows tiny overpotentials of 48 and 209 mV for hydrogen evolution reaction (HER), 238 and 514 mV for oxygen evolution reaction (OER) at 10 and 1000 mA cm −2, respectively. Moreover, Am−Mo−NiS0.5 Se0.5 delivers excellent stability for at least 300 h without obvious degradation. Theoretical calculations revealed that the Ni sites in the defect‐rich amorphous structure of Am−Mo−NiS0.5 Se0.5 owns higher electron state density and strengthened the binding energy of H2 O, which will optimize H adsorption/desorption energy barriers and reduce the adsorption energy of OER determining step. Abstract : Am−Mo−NiS0.5 Se0.5 nanocomposites were synthesized by a simple one‐step strategy. The catalysts display efficient and stable bifunctional electrocatalytic performance for HER and OER, as well as for water splitting in neutral solution. The amorphous structure abundant unsaturated sites altered the local electronic structure of metallic sites and optimized the energy barrier for the rate‐determining step (O* to OOH*).